Norma brasileira de comercialização de alimentos para lactentes e crianças de primeira infância: histórico, limitações e perspectivas Brazilian guidelines for marketing baby food: history, limitations and perspectives - Renata Monteiro (Pan American Health Organization, 2006)
The objective of this paper is to present and discuss Brazilian policy concerning actions to protect breastfeeding, especially the history, international and national background, limitations, and perspectives of the Brazilian Guidelines for the Marketing of Baby Food, Pacifiers and Bottles. The Brazilian Guidelines, which play a crucial role in protecting breastfeeding against industry marketing strategies, were based on the International Code of Marketing of Breastmilk Substitutes, proposed by the World Health Organization in 1981. The first version of the Brazilian Guidelines was released in 1988, and there were subsequent revisions in 1992 and 2001/2002. In 2006, the Guidelines became national law. However, the strides made over this period in terms of regulation have been few because the law is not always observed. Thus, it is essential that all actors involved, including government officials, manufacturers and sellers of baby food and other baby products, teaching and health professionals and their associations, international bodies, and non-governmental organizations make a commitment to enforce the current law.